Effect of process parameters on tensile strength of 3D printed PLA parts - Abdul Hamid, Rahimah; Maidin, Shajahan; Mohd Yussoff, Nurul Hajar; Ng, Pei Lee; Tsutomu, Ito (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Additive Manufacturing (AM), known as 3D printing, has transformed industrial production through precise layer-by-layer material deposition. However, the primary issue often encountered during the fabrication of parts using Fused Deposition Modeling (FDM) is the inferior mechanical characteristics resulting from processing parameters. This study investigates the effect and interaction of various process parameters (infill density, temperature, layer height) on the tensile strength of 3D-printed PLA parts using Analysis of Variance (ANOVA). Utilizing a fractional factorial design, four-parameter runs with three factors at two levels each were created. The main plot effect indicates that infill density and print temperature are the most significant factors, and the interaction plots reveal a notable correlation between printing temperature and layer height. A linear regression model has been developed to predict the tensile strength. The selected process parameters influence the strength, but only infill density (85.03%) and print temperature (8.8%) are statistically significant. The microstructure analysis showed a good agreement between the experimental and statistical data, where 100% infill density at different temperatures and layer height settings offer excellent interlayer adhesion and fewer voids than the 50% infill density. The presented methodology can be used as a pre-processing approach to optimize desired mechanical propertiesin material extrusion 3D printing.